(untitled) (Iranian Journal of Kidney Diseases, 2010)
Hypophosphatemia is defined as a serum phosphate level of less than 2.5 mg/dL (0.8 mmol/L). Hypophosphatemia is caused by inadequate intake, decreased intestinal absorption, excessive urinary excretion, or a shift of phosphate from the extracellular to the intracellular compartments. Renal phosphate wasting can result from genetic or acquired renal disorders. Acquired renal phosphate wasting syndromes can result from vitamin D deficiency hyperparathyroidism, oncogenic osteomalecia, and Fanconi syndrome. Genetic disorders of renal hypophosphatemic disorders generally manifest in infancy and are usually transmitted as an X-linked hypophosphatemic rickets. Symptoms of hypophosphatemia are nonspecific and most patients are asymptomatic. Severe hypophosphatemia may cause skeletal muscle weakness, myocardial dysfunction, rhabdomyolysis, and altered mental status. The diagnostic approach to hypophosphatemia should begin with the measurement of fractional phosphate excretion; if greater than 15% in the presence of hypophosphatemia, the diagnosis of renal phosphate wasting is confirmed. Renal phosphate wasting can be divided into 3 types based upon serum calcium levels: primary hyperparathyroidism (high serum calcium level), secondary hyperparathyroidism (low serum calcium level), and primary renal phosphate wasting (normal serum calcium level). Phosphate supplementations are indicated in patients who are symptomatic or who have a renal tubular defect leading to chronic phosphate wasting. Oral phosphate supplements in combination with calcitriol are the mainstay of treatment. Parenteral phosphate supplementation is generally reserved for patient with life-threatening hypophosphatemia (serum phosphate < 2.0 mg/dL). Intravenous phosphate (0.16 mmol/kg) is administered at a rate of 1 mmol/h to 3 mmol/h until a level of 2 mg/dL is reached.